MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE FUNDS: WITH TRANSPARENCY AND ACCOUNTABILITY - Leni Deli (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
this research is quantitative with an associative approach, where data is collected through questionnaires distributed to 60 respondents consisting of school principals, treasurers, and school operational staff. The results showed that transparency and accountability have a positive and significant effect on the management of BOS funds. The test results indicate that transparency has a significant effect with a t-statistic value of 7.360 and accountability with a t-statistic value of 3.133. In addition, simultaneously, transparency and accountability significantly influence the management of BOS funds with an F-statistic value of 24.545. This research is expected to contribute to improving the management of educational funds in Indonesia through the application of transparency and accountability principles